Word And Syllable - Sri Ayu Fatmawati; Yoga Fadhillah; Yani Lubis (BADAN PENERBIT STIEPARI PRESS, 2023)
In the English language, spelling and pronunciation have a particularly strange relationship. How we write a word and how we say it often do not match. There always seem to be discrepancies and exceptions to the rules of thumb. When we say a word, the sounds we make naturally consist of word parts. We call these parts ‘syllables’. A syllable can be defined as any one of the parts into which a word is naturally divided when it is pronounced. Hence, we might sat that phonetically (i.e. in relation to the way it is pronounced), a syllable is a unit of organization for a sequence of speech sounds. It is made up of a centre of syllable, called a nucleus (mostly a vowel), with optional initial and final sounds (typically, consonants). English pronunciation of words isn’t always intuitive. The same letter combinations in one word may make a completely different sound in another. One way to practice your pronunciation is by breaking words down into syllables. Syllables are the sonic units of a word, sometimes called the “beats” of a word. We do this naturally when we speak. Every time you say a new syllable, your mouth has to change its shape and make a new sound. Noticing when this happens and counting syllables can help you break words down into recognizable patterns that are easier to pronounce.